Confining perovskite quantum dots in the pores of a covalent-organic framework: quantum confinement- and passivation-enhanced light-harvesting and photocatalysis. Issue 43 (1st November 2021) - Meng, Genping; Zhen, Liping; Sun, Shihao; Hai, Jun; Zhang, Zefan; Sun, Dina; Liu, Qiang; Wang, Baodui
Abstract : Monodisperse CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) were encapsulated into the ordered mesopores of a thiol-functionalized covalent-organic framework (COF-SH) to construct highly efficient artificial light-harvesting systems. Abstract : All-inorganic lead halide perovskites have attracted significant attention in artificial light-harvesting systems (ALHSs) due to their superior emission tunability and high light-absorption coefficients. However, their relatively low photoluminescence quantum yield (PLQY), surface defects, and poor thermal and air stability severely hinder their actual applications. Here, we demonstrate a simple and versatile method to grow monodisperse CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) into the ordered mesopores of a thiol-functionalized covalent-organic framework (COF-SH) as emission-tunable antennas. Intriguingly, benefiting from the quantum confinement and defect-passivation, the resulting CsPbX3 @COF-SH not only presents dramatically improved environmental and thermal stability, but also exhibits enhanced PLQY (30.2%), significantly higher than that of pristine CsPbX3 perovskite bulk crystals (less than 1.0%). Importantly, the emission spectra of antennas could be precisely tuned by tailoring the halogen component to achieve the well-matched intersections between the emission peak of the antennas and the absorption peak of eosin Y (ESY) or rose bengal (RB) acceptor in ALHSs. As a result, the efficiency of energy transfer achieved from CsPbBr3 @COF-SH to ESY and from CsPbBr2 I@COF-SH to RB reached up to 94.4% and 93.6%, respectively. To better imitate natural photosynthesis, ESY-CsPbBr3 @COF-SH and RB-CsPbBr2 I@COF-SH systems were employed as photochemical catalysts for C–H selenation and cross-coupling/annulation reactions, respectively, and both systems showed elevated catalytic activity with excellent yields of up to 99.3% and 95.5% and far surpassing that of ESY or RB alone. This work clearly demonstrates the great advantages of COFs in the fabrication of embedded perovskite QDs with enhanced photoluminescence, thereby facilitating light-harvesting and promoting light-converting applications.